Английский бульвар: роман / Чингиз Абдуллаев - Абдуллаев Чингиз Акифович (Спецсериал "Сыщики", 2002)
Экземпляры: ф.22 (20181024) / Инвентарный номер: 58683 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44